Field Test Research on Red Clay Slope under Atmospheric Action. (20th May 2021) - Chen, Kaisheng
Abstract : By embedding water content sensors and pore water pressure sensors inside the red clay slope on-site in Guiyang, Guizhou, shear tests were performed on soil samples at different depths of the slope under different weather. The changes of water content, pore water pressure, and shear strength index of the slope inside the slope under the influence of the atmosphere were tracked and tested, and the failure characteristics and evolution of the red clay slope were analyzed. It is believed that the depth of influence of the atmosphere on red clay slopes is about 0.7 m, rainfall is the most direct climatic factor leading to the instability of red clay slopes, and the evaporation effect is an important prerequisite for the catastrophe of red clay slopes. The cohesion and internal friction angle of the slope soil have a good binary quadratic function relationship with the water content and density. The water content and density can be used to calculate the cohesion and internal friction angle. Failure characteristics of red clay slopes: the overall instability failure is less, mainly surface failure represented by gullies and weathering and spalling, and then gradually evolved into shallow instability failure represented by collapse and slump. The damage evolution law is as follows: splash corrosion and surface corrosion stage⟶ fracture development stage⟶ gully formation stage⟶ gully development through stage⟶ local collapse stage⟶ slope foot collapse stage.